Anaemia in term pregnancy: influence on maternal and perinatal outcome and role of demographic factors - Miglani, Urvashi; Bhangadia, Priya; Kadam, V. K.; Laul, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to study maternal and perinatal outcome and various demographic factors in term pregnancy complicated with anaemia at DDU Hospital. Methods: Hospital based prospective observational analytical study. 200 pregnant women reporting to antenatal clinic or admitted to the Hospital in labour/not in labour after 36+6weeks of pregnancy were taken as study subjects. Study duration was one year between July 2017 to June 2018. Results: The prevalence of mild, moderate and severe anaemia was 25%, 56% and 19% respectively. Education status, socioeconomic status, ANC visit, interpregnancy interval were significantly associated with anemia(p<0.05). Significant association was observed between occurrence of PPH and severity of anaemia(OR 12.77; CI 2.32 to 70.12). The incidence of LBW increased with severity of anaemia. (OR-6.25;CI 2.6 to 15). There was a statistically significant difference found in prevalence of IUGR babies. The risk of Apgar score <8 increased with severity of anaemia. Perinatal mortality was observed in 8% subjects with anaemia as compared to 3% in subjects without anaemia. Conclusions: Maternal anaemia is a major public health problem. Simple steps taken to correct anaemia in female contemplating pregnancy and pregnant women can definitely have far reaching influences on maternal and perinatal morbidity.